Indications, complications, and outcomes of cardiac surgery after heart transplantation: results from the cash study - Gökler, Johannes; Aliabadi-Zuckermann, Arezu Z.; Kaider, Alexandra; Ambardekar, Amrut V.; Antretter, Herwig; Artemiou, Panagiotis; Bertolotti, Alejandro M.; Boeken, Udo; Brossa, Vicens; Copeland, Hannah; Generosa Crespo-Leiro, Maria; Eixeré-Esteve, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2022)
Allograft pathologies, such as valvular, coronary artery, or aortic disease, may occur early and late after cardiac transplantation. Cardiac surgery after heart transplantation (CASH) may be an option to improve quality of life and allograft function and prolong survival. Experience with CASH, however, has been limited to single-center reports.
Gesehen am 29.08.2022